Quality of Mathematics Even Semester Final Assessment Test in Class VIII Using R Program - Rahmadani, Nadilla; Hidayati, Kana (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
This study was conducted using the Item Responses Theory (IRT) method with R program to comprehensively analyze quality of Mathematics Even Semester Final Assessment test in class VIII for 2021/2022 Academic Year. This assessment was created through a collaborative effort involving mathematics teachers from a Public Junior High School in Binjai. It consists of 20 multiple-choice questions, each with four alternative answers. Furthermore, the study followed a descriptive framework carried out by a quantitative methodology. The data source was the responses of 189 students in class VIII who took part in Mathematics Even Semester Final Assessment for the 2021/2022 Academic Year, collected using documentation methods. The results showed that the items developed by the teacher: (1) were most appropriate for analysis using a two-parameter logistic model (2-PL), (2) distribution of material achieved during the even semester on the item tested was uneven, (3) eight of the 20 item was acceptable and kept in the question bank, while the remaining 12 were of poor quality; (4) the item fell into the category of easy to moderate difficulty, dominated by item in the moderate category, and (5) Mathematics Even Semester Final Assessment in class VIII provided accurate information regarding students’ mathematics ability at moderate ability levels ( to ). DOI: https://doi.org/10.22342/jpm.17.3.20627.397-417